การพัฒนาตัวบ่งชี้สมรรถนะของนักเทคโนโลยีการศึกษา - ชไมพร อินทร์แก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
The development of professional competencies in educational technology increases the potential of work efficiency in accordance with the criteria and in accordance with educational technology standards. These are the strengthening and stability of the profession for survival and sustainability of the educational technology profession in the disruptive technology era.The purposes of this research were 1) to develop of competency indicators for educational technologists and to test the goodness of fit between the developed competency indicators model and the empirical data 2) to study and analyze the competency level of educational technologists and 3) to propose the competency indicators of educational technologists. The research was used as a qualitative research methodology. The sample used in the research consisted of 10 experts, 10 stakeholders, and 985 educational technologists which were selected by multi-stage randomization. The research tools used were semi-structural interview forms, a five-point rating scales questionnaire, and a competency Indicator certification assessment form. Data were analyzed with descriptive statistics, exploratory factor analysis and confirmatory factor analysis and a one-way analysis of variance (f-test). The research results were as follows:The results of the research revealed that 1) the development of competency indicators of educational technologists received 5 factors, 14 indicators which were the first competency, professional knowledge of educational technology, two indicators, the second competency, characteristics of educational technologists, three indicators, the third competency, professional skills in educational technology, three indicators, the fourth competency, management and organization of learning environments, three indicators, and the fifth competency, professional development for lifelong learning, three indicators.The results of second order confirmatory factor analysis competency indicators model found that the model was valid and fitted with the empirical data (Chi-Square=33.27 , df = 30, p = 0.311, AGFI = 0.98, SRMR = 0.013, RMSEA = 0.011, CN = 1501.43). The factor loadings of 5 factors were positive at 0.01, ranging in size from 0.73 – 0.96. The highest factor loading was on the professional skills in educational technology (0.96), management and organization of learning environments (0.92), professional development for lifelong learning (0.84), professional knowledge of educational technology (0.78), and characteristics of educational technologists (0.72) respectively. 2) The results of the analysis of competency level of educational technologists found that the second competency, characteristics of the educational technologists were at highest level of overall competencies because educational technologists places great emphasis on ethical conduct and positive professional attitudes, emotional traits and living with others in society including critical thinking, problem solving, and creativity. However, the other competencies in overall were in moderate levels due to educational technologists lack of professional development skills in digital media technology and the comparison of the competency level classified by age range and work experience with analysis of variance (One-way ANOVA) found that the competency of educational technologists classified by overall age and in each of the 5 competencies were significantly different at 0.05 levels and the competency classified by working experience in educational technology as a whole and in each competency were significantly different at  levels of 0.01 and 0.05. In other words, educational technologists with a greater age range and work experience had a higher competency than educational technologists with a lower age range and work experience. 3) The assessment of the certification of the development of competency indicators for educational technologists results have shown that the development of such indicators were in the most appropriate level (Mean = 4.97, S.D. = 0.06) and can be applied in actual practices.